Lithium Titanate/Carbon Nanotubes Composites Processed by Ultrasound Irradiation as Anodes for Lithium Ion Batteries - João Coelho (Nature Portfolio, 2017)
Abstract In this work, lithium titanate nanoparticles (nLTO)/single wall carbon nanotubes (SWCNT) composite electrodes are prepared by the combination of an ultrasound irradiation and ultrasonic spray deposition methods. It was found that a mass fraction of 15% carbon nanotubes optimizes the electrochemical performance of nLTO electrodes. These present capacities as high as 173, 130, 110 and 70 mAh.g−1 at 0.1C, 1C, 10C and 100C, respectively. Moreover, after 1000 cycles at 1C, the nLTO/SWCNT composites present a capacity loss of just 9% and a Coulombic efficiency of 99.8%. Therefore, the presented methodology might be extended to other suitable active materials in order to manufacture binder free electrodes with optimal energy storage capabilities.